Vascular endothelial growth factor receptor 2 (VEGFR-2) plays a key role in vasculogenic mimicry formation, neovascularization and tumor initiation by Glioma stem-like cells. - Xiaohong Yao; Yifang Ping; Ying Liu; Kequiang Chen; Teizo Yoshimura; Mingyong Liu; Wanghua Gong; Chong Chen; Qin Niu; Deyu Guo; Xia Zhang; Ji Ming Wang; et al. (PLoS ONE)
Human glioblastomas (GBM) are thought to be initiated by glioma stem-like cells (GSLCs). GSLCs also participate in tumor neovascularization by transdifferentiating into vascular endothelial cells. Here, we report a critical role of GSLCs in the formation of vasculogenic mimicry (VM), which defines channels lined by tumor cells to supply nutrients to early growing tumors and tumor initiation. GSLCs preferentially expressed vascular endothelial growth factor receptor-2 (VEGFR-2) that upon activation by VEGF, mediated chemotaxis, tubule formation and increased expression of critical VM markers by GSLCs. Knockdown of VEGFR-2 in GSLCs by shRNA markedly reduced their capacity of self-renewal, forming tubules, initiating xenograft tumors, promoting vascularization and the establishment of VM. Our study demonstrates VEGFR-2 as an essential molecule to sustain the "stemness" of GSLCs, their capacity to initiate tumor vasculature, and direct initiation of tumor.